2020
DOI: 10.2147/tcrm.s210648
|View full text |Cite
|
Sign up to set email alerts
|

<p>Therapeutic Potential of Dupilumab in the Treatment of Chronic Rhinosinusitis with Nasal Polyps: Evidence to Date</p>

Abstract: Chronic rhinosinusitis with nasal polyposis (CRSwNP) is one of the most severe forms of chronic rhinosinusitis. CRSwNP is characterized by nasal and facial congestion, loss of sense of smell, rhinorrhea, and post-nasal drip. Treatments have been ineffective at controlling disease recurrence, despite multiple courses of medical and surgical therapies. Oral glucocorticoid therapy is often used to control exacerbations leaving the patient exposed to steroid-induced adverse effects. Thus, there is a clear unmet ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
1
22
0
2
Order By: Relevance
“…Dupilumab is a fully human monoclonal antibody targeting the α-chain subunit of IL-4 receptors (Type 1 and type 2 IL-4Rα) and inhibiting IL-4/IL-13 signaling 35 . Literature data [42][43][44] have demonstrated that the dual inhibition of IL-4 and IL-13 signaling may represent an important strategy for the treatment of type 2 CRSwNP. Bachert et al 35 dupilumab had a significant reduction in polyp size (primary endpoint), which was clinically observable from the 4th week of treatment.…”
Section: Anti-il-4/il-13: Dupilumabmentioning
confidence: 99%
“…Dupilumab is a fully human monoclonal antibody targeting the α-chain subunit of IL-4 receptors (Type 1 and type 2 IL-4Rα) and inhibiting IL-4/IL-13 signaling 35 . Literature data [42][43][44] have demonstrated that the dual inhibition of IL-4 and IL-13 signaling may represent an important strategy for the treatment of type 2 CRSwNP. Bachert et al 35 dupilumab had a significant reduction in polyp size (primary endpoint), which was clinically observable from the 4th week of treatment.…”
Section: Anti-il-4/il-13: Dupilumabmentioning
confidence: 99%
“…Patients with serious disease or who have failed medical management may be eligible for sinus surgery. Functional endoscopic sinus surgery (FESS) can improve sinonasal symptoms and inflammation, but NP may still recur 9 , with rates as high as 50% (for patients observed over a period of 3 years) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with serious disease or who have failed medical management may be eligible for sinus surgery. Functional endoscopic sinus surgery (FESS) can improve sinonasal symptoms and inflammation, but NP can still recur 8 , with rates as high as 50% (for patients followed over a period of 3 years) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the unmet need in recalcitrant CRSwNP, biologics have emerged as a novel treatment option owing to recent advancements in our understanding of the disease, particularly inflammation 9,10 . Studies have demonstrated efficacy for biologics in the treatment of CRSwNP; therefore, biologics are anticipated to reduce the clinical, humanistic and economic burden of CRSwNP.…”
Section: Introductionmentioning
confidence: 99%